VALIDITAS HANDOUT BIOLOGI TERINTEGRASI AYAT-AYAT AL-QUR’AN PADA MATERI ANIMALIA SMA/MA - Diah Putri Anggun; Rahmawati Rahmawati (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2022)
The lack of availability of biology learning materials integrated by Qur'an's verses, especially in biology subjects, even though Indonesia has the largest number of moeslim in the world. We should have variations of learning materials integrated by Quran’s verses to help students understand biology subject matter that is integrated by Quran’s verses. The aim of study was test the validity of the biology handouts on animalia material for SMA/MA. This type of research was research and development using the Plomp model. This research is limited to two phases, namely the prelimanary research and the prototype phase. The data collection technique was obtained from the validation sheet. Validation was carried out by four validators, namely media, linguists, material , and experts in interpreting Quran’s verses. Based on the validation stage, the results were very valid for the four fields, namely media (3.63), language (3.25), material (3.62), and interpretation of the Quran’s verses (3.67). Thus, it can be concluded that the integrated biology handout of the verses of the Qur'an on animalia material is declared very valid.